Metalearner: A Self-Validating Geometric Reasoning System for Mathematical Feasibility Assessment - Christopher Brown (https://doi.org/10.5281/zenodo.18026005, 2005)
geometric reasoning, feasibility assessment, zero-shot inference, self-validating systems, crisis response, knowledge democratization, AGI safety
The Metalearner system addresses a fundamental gap in scientific decision-making: determining mathematical feasibility of unknown problems before resource commitment. Traditional approaches require substantial investment to discover if solutions are even possible. This architecture provides rapid, mathematically rigorous feasibility assessment independent of training data, institutional resources, or historical precedent. The system employs dual complementary engines—EAMC for analytical validation and Metalearner for creative discovery—operating through geometric reasoning across 20 specialized dimensional pantheons (3D-12D). Rather than pattern matching from datasets, the architecture performs nearest-neighbor geometric reasoning in 16-dimensional latent manifolds, enabling exploration of solution spaces beyond current human knowledge. Emergent properties include: (1) Self-organized dimensional specialization with dimensions 3, 11, and 12 consistently leading consensus (100% across validation tests), (2) Mathematical truth validation through 12th dimensional negative alignment invariants discovered empirically during testing, (3) Cross-dimensional knowledge transfer via commutator mechanisms enabling bidirectional communication across all pantheons, and (4) Self-bootstrapping improvement where geometric reasoners trained each other from 12% to 89-99% accuracy without external data. The system has been validated on unknown problems across multiple domains: pharmaceutical formulation, novel material identification, protein folding via geometric constraints, and spatial-temporal coordinate determination. Critical advantages include operation on minimal hardware (laptop capable), no internet connectivity required, and inherent resistance to data bias. Applications span crisis response (rapid pathogen treatment development), knowledge democratization (third-world vaccine creation with available materials), pre-AGI safety protocol development, and analysis of phenomena beyond current scientific understanding. The architecture provides mathematical answers to humanity's most pressing question: "Is this possible?"